The association between self-reported nocturnal sleep duration, irregularity in daily energy intake and diet quality in a sample of Iranian adults - Vida Yazdani; Sheida Zeraattalab-Motlagh; Ahmad Jayedi; Maryam Majdi; Amin Mirrafiei; Fahimeh Martami; Kurosh Djafarian; Sakineh Shab-Bidar (Cambridge University Press, 2023)
Abstract Objective: Evidence on the relationship between sleep duration and irregularity in daily energy intake with diet quality in Iranian adults is scarce. We aimed to evaluate the association of sleep duration with diet quality and irregularity in daily energy intake. Design: This is a cross-sectional study. Setting: The study was performed in healthcare centres in Tehran. Participants: 739 adults aged 20-59 years were recruited. Dietary intake was assessed by a FFQ and three 24-h dietary recalls. Diet quality was assessed using the Healthy Eating Index-2015 (HEI-2015). An irregularity score of daily energy intake was calculated based on the deviation from the 3-d mean energy intake. Sleep duration was estimated using self-reported nocturnal sleep duration by each person. Results: The mean age of the study participants was 44·4 ± 10·7 years; 70 % were women. The mean nocturnal sleep duration, HEI score and irregularity score were 6·7 ± 1·22 h/d, 52·5 ± 8·55 and 22·9 + 19, respectively. After adjusting for potential confounders, sleep duration was not associated with adherence to HEI-2015 (OR: 1·16; 95 % CI 0·77, 1·74). Longer sleep duration was marginally associated with a lower odd of irregularity in daily energy intake. However, after adjustment for various confounders, this association was not significant (OR: 0·82; 95 % CI 0·50, 1·33; P trend = 0·45). No significant interaction was observed between sleep duration and irregularity in daily energy intake in relation to adherence to HEI-2015 (P interaction = 0·48). Conclusions: We found that sleep duration was not associated with adherence to HEI-2015 and irregularity in daily energy intake. Further prospective studies are warranted.